A methods engineering study on Dakki Classic Concepts Incorporated - Collado, Hazel Kristine M.; Langaoen, Sharon M.; Yarcia, Godofredo Julius P. (Diliman, Quezon City College of Engineering, 2004)
The group was able to point out and confirm by analysis the areas and methods that need to be improved. They were able to come up with recommendations for each of the problems that they identified. One major problem that the group has observed is the difficulty in vacuum-packing the pillows using the manual compressor. This is also confirmed by the workers. Frequent bending has caused back pains to most of them. It was then proposed that the management should purchase another mechanized compressor to replace those that are handled manually. The machine costs Php250,000 pesos with useful life of five years. The company would be incurring a cost of 41667.67 pesos per month for the purchase of this machine but with this machine in use, the company can do away with two workers per month handling a manual compressor. Since the labor unit cost of these two workers per month is 14560 pesos, the company would actually be saving 10,393.33 pesos per month. Having this machine will be a lot cheaper and will increase the production by 1434 pillows per day. The group has also proposed a new layout for the second floor of the plant. The retail section is moved from the far corner of the floor and is brought nearer to the slide and stairs. The cutting section is also suggested to be moved near the fabric rolls. The method in inverting the pillowcases is made simpler by folding each pillow case right after inverting them. This method, compared with the present where worker folds the pillow after the whole batch has been inverted, is more efficient. Inspection procedure must also be reinforced. It was also observed that those in quality control are oftentimes leaving their inspection areas to help on operations experiencing bottle necking. Quality must never be sacrificed so the inspection method must never be neglected. The forms used are also analyzed to see the significance of each. The Delivery Receipt form is suggested to be eliminated since it is used only for recording the number of packaging tapes handed by the Central Warehouse to the branches. To reduce the cost, the company may opt to eliminate this form and have the entry on it be recorded in the Purchase Order Slip, a form used to track the quantities of pillows given to branches. The Issuance Slip is also redesigned to have the minimum number of signatures needed. The "Requested by" and "Received by" entry are combined since the same person signs them. Moreover, it was suggested that the president need not sign this form. The approval from the warehouse manager is enough since he already have enough knowledge on this matter. Other recommendations include the use of carts in transporting pillows from the workstation to another, use of tweezers or stick in pulling out pillow sides and reweighing of fiber before stuffing.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32: Methods engineering
Keywords: Systems analysis